EVALUASI KINERJA TRAYEK TRANSJOGJA DENGAN MENGGUNAKAN SOFTWARE EMME/3 (Studi kasus : Kota Yogyakarta) - , NURMALIA, Prof. Dr-Ing. Ir. Ahmad Munawar, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Transjogja is one of the Government's program of Yogyakarta special region Province in order to find a solution to resolve the issues of transport in Yogyakarta, in particular by creating a program that aims to reform the system of deposit with the buy the service system. A bus system that is fast, secure and convenient as well as related time has the precision of a much better compared to other public transport because it is supported by the infrastructure, scheduling as well as good vehicles. Research begins with the road network modeling on existing condition by using a transport simulation software EMME/3. Then the process is carried out charging a running origin-destination matrix (O-D Matrix) passengers in 2011 on a road network that would accrue to some parameters for validation tests such as the number of fleet, the number of passengers, load factor, and the travel time. The validation is performed by comparing the result of observed data and the field data. After the validation test indicates a good value (R 2 â 1) the next step is to create the new model with the process of optimisation of fleet on their respective routes to generate performance routes. Validation of existing conditions in order to get the performance of a good transjogja, it has been shown in the value of the last validation (fourth) with a value of R 2 on each parameter, i.e. the number of passengers/rit = 0.539, load factor = 0.494, travel time = 0.673, and fleet = 1. Whereas, the new model (model 2) recommended for improving the performance of Transjogja, the number of routes each the fleet routes i.e. the route of 1A = 12 fleet, the route of 1B = 6 fleet, the route of 2A = 7 fleet, the route of 2B = 8 fleet, the route of 3A = 11 fleet, the route of 3B = 10 fleet. So with the optimized number of fleet turned out to be the result of analysis stating for the model 2 is better so it can be proposed to improve the performance of the Transjogja Route which will come despite having difference comparison which is not too far with models 1 (existing models). It is seen from the third parameters comparison headway, load factor, and the number of passenger/bus/trip made by a public vehicle.